Development and Characterization of Effervescent Granules Containing Cinnamomum burmanii Ethanolic Extract with Potent Antioxidant Activity - Rima Rahmawati; Rika Yulianti; Indra Indra (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2026)
The study aimed to develop effervescent granules containing Cinnamomum burmanii extract with strong antioxidant activity, good physicochemical stability, and consumer acceptability. Ethanolic extraction was employed to maximize the recovery of phenolic and flavonoid compounds, followed by formulation through controlled wet granulation using citric acid, tartaric acid, sodium bicarbonate, polyvinylpyrrolidone, and aspartame. The resulting extract showed potent antioxidant capacity with an IC₅₀ of 7.82 ppm, indicating high radical-scavenging activity. Three formulations (F1–F3) were evaluated for physical properties, dissolution, pH, and sensory characteristics. The optimized formulation (F3) demonstrated rapid effervescence (<3 minutes), suitable acidity (pH 3.7–4.2), low moisture content (<5%), and strong consumer acceptance. Although antioxidant activity slightly decreased after granulation (IC₅₀ ≈ 69 ppm), the product maintained significant efficacy and stability. These results confirm that ethanol extraction combined with optimized wet granulation effectively produces a stable, functional, and palatable herbal effervescent formulation. The study establishes a scientific basis for converting C. burmanii into a modern nutraceutical product and supports its potential application in antioxidant beverages. Future work should explore bioavailability enhancement and synergistic formulations with other botanical extracts to maximize therapeutic value and product performance.